2015
DOI: 10.15585/mmwr.mm6433a3
|View full text |Cite
|
Sign up to set email alerts
|

School-Level Practices to Increase Availability of Fruits, Vegetables, and Whole Grains, and Reduce Sodium in School Meals — United States, 2000, 2006, and 2014

Abstract: U.S. schools need updated kitchen equipmentThe Kids' Safe and Healthful Foods Project is a collaboration between The Pew Charitable Trusts and the Robert Wood Johnson Foundation that provides nonpartisan analysis and evidence-based recommendations on policies that impact the safety and healthfulness of school foods. For more information, see healthyschoolfoodsnow.org.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 6 publications
1
21
0
4
Order By: Relevance
“…As described below, five of seven studies found that there was a positive salt‐related outcome as a result of either nutrition standards in hospitals and schools, lower sodium foods provided in a University canteen, or behavioral interventions . The two studies that found a non‐significant change in salt intake were both broader behavioral interventions: one mobile phone–based intervention that aimed to improve the cardiometabolic profile in 553 pre‐hypertensive participants and the other included the provision of cooking lessons to improve the overall diet quality of parents and their children …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As described below, five of seven studies found that there was a positive salt‐related outcome as a result of either nutrition standards in hospitals and schools, lower sodium foods provided in a University canteen, or behavioral interventions . The two studies that found a non‐significant change in salt intake were both broader behavioral interventions: one mobile phone–based intervention that aimed to improve the cardiometabolic profile in 553 pre‐hypertensive participants and the other included the provision of cooking lessons to improve the overall diet quality of parents and their children …”
Section: Resultsmentioning
confidence: 99%
“…The two studies evaluating the impact of real‐world nutrition standards for foods sold in institutional settings demonstrate a trade‐off between validity of the outcome measurement and generalizability of the study findings. While the study by Merlo and colleagues was nationally representative of schools, the study outcome relied on schools themselves reporting whether they had adopted salt‐lowering practices, which is subject to a high risk of self‐reporter bias. Moran and colleagues used a more objective measurement and derived the sodium content of meals based on foods on hospital menus; however, it was limited to eight hospitals that were participating in the Healthy Hospital Food Initiative, so the impact of the program on all other hospitals is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…43 However, opportunities exist to improve school meal standard implementation. 44 Interventions targeting the home environment have also been shown to increase fruit and vegetable intake among adolescents. 45;46 …”
Section: Discussionmentioning
confidence: 99%
“…According to the Centers for Disease Control and Prevention's latest report, hopefully the trends seen in foods offered in the school lunch program will have a positive impact. 1 But, when the cultural norm is ''all you can eat'' for the dollar, and inner aisles of grocery stores are expanding and lined with tempting foods, many nonessential for a good and tasty diet, you know we have a lot of work to do. Already reports by the Government Accountability Office have described the difficulties faced in implementing the new standards.…”
Section: Nutrition and Food Policymentioning
confidence: 99%
“…1 Theses recommendations support the overall public health goal to reduce risk of weight gain, obesity, diabetes, and other diseases. While the healthful trends in food offerings are positive, school lunches have historically been criticized as unappetizing and not very healthy (eg, too many fried foods).…”
mentioning
confidence: 97%